Predictors of Medication Non-Adherence Among Hepatitis B Patients in South Sudan: A Health-Facility-Based Cross-Sectional Study - Afolabi IB; Aremu AB; Koryom MJP; Buh A; Bainbridge SA; Phillips KP (Patient Preference and Adherence)
Ismail Bamidele Afolabi,1,2 Abdulmujeeb Babatunde Aremu,3 Musa Jal-Paul Koryom,1,4 Amos Buh,2 Shannon A Bainbridge,2,5 Karen P Phillips2 1Department of Public Health, Cavendish University, Kampala, Uganda; 2Interdisciplinary School of Health Sciences, University of Ottawa, Ottawa, Ontario, Canada; 3Department of Public Health, Islamic University in Uganda, Mbale, Uganda; 4Department of Public Health, Juba Teaching Hospital, Juba, South Sudan; 5Department of Cellular and Molecular Medicine, University of Ottawa, Ottawa, Ontario, CanadaCorrespondence: Ismail Bamidele Afolabi, Email iafol063@uottawa.caBackground: Despite the effectiveness of hepatitis B virus (HBV) antiviral treatment therapy in reducing the risk of liver-related complications, such as cirrhosis and hepatocellular carcinoma among chronically infected patients, medication non-adherence continues to hamper the successful management of the infection. The extent of HBV treatment adherence, associated facilitators, and barriers in South Sudan is not established. This study aimed to explore the predictors of medication non-adherence among HBV patients attending a public health facility in, South Sudan.Methods: We conducted a facility-based cross-sectional study of 392 convenience-selected patients using a pretested interviewer-administered questionnaire premised on the information-motivation-behavioral skills (IMB) adherence model between December 2023 and March 2024. The relationship between medication non-adherence and antecedent variables was ascertained by logistic regression analysis.Results: The sample was predominantly male (64.3%), and the mean age was 31.06 (30.19– 31.93) years, with 28.1% reporting no formal education. The patients demonstrated inadequate HBV information (4.33± 1.93), low motivation (8.20± 2.69), and inadequate behavioral skills toward medication adherence (8.45± 2.99), as measured on their respective rating scales. Further, more than two-thirds of the patients (70.2%) were HBV medication non-adherent. Younger age (AOR = 4.74, 95% CI = 2.13– 10.56), being currently unmarried (AOR = 3.25, 95% CI = 1.76– 6.01), unemployment (AOR = 4.19, 95% CI = 1.84– 9.56), and increased behavioral skills (AOR = 1.12, 95% CI = 1.84– 9.56) significantly influenced medication non-adherence. Lower education (AOR = 0.21, 95% CI = 0.10– 0.46) and information adequacy (AOR = 0.63, 95% CI = 0.53– 0.75) were associated with lower odds of non-adherence.Conclusion: The study highlights key factors influencing the concerning rate of medication non-adherence among HBV patients in South Sudan. While these identified factors may explain the lingering burden of HBV-related complications, targeted interventions addressing demographic, socioeconomic barriers, and HBV-specific education are essential to enhance adherence and improve health outcomes.Keywords: hepatitis B, treatment therapy, medication non-adherence, information adequacy, behavioral skills, South Sudan